Project Based Learning (PJBL) dalam Meningkatkan Kemandirian Belajar Mahasiswa - Wahyuddin Wahyuddin; Ernawati Ernawati; Hamdana Hadaming; Maharida Maharida; Muhammad Awal Nur (Jurnal Penelitian dan Pembelajaran Matematika, 2026)
This study aims to analyze the impact of Project-Based Learning (PjBL) implementation on enhancing students' learning autonomy. Employing a quantitative survey method and Structural Equation Modeling (SEM) analysis, this research examines the relationship between PjBL implementation and students' learning autonomy levels. A total of 136 students from a private university in Indonesia participated as the sample. The results indicate that PjBL significantly influences the improvement of students' learning autonomy, with a path coefficient of 0.716 and a highly significant p-value (p < 0.001). The findings conclude that PjBL has a significant effect on increasing students' learning autonomy. PjBL has proven to be effective in encouraging students to manage tasks, think critically, make independent decisions, and develop essential skills such as time management, problem-solving, and self-reflection, which are crucial elements in student-centered learning. In addition to academic skills, PjBL also plays a role in the development of soft skills such as teamwork, communication, and independent project management. Practical experiences in projects relevant to real-life scenarios make students more independent, confident, and responsible for their learning outcomes. However, this study also identifies challenges in PjBL implementation, such as time constraints, limited resources, and insufficient instructor support. Although PjBL is effective in fostering learning autonomy, its success requires careful planning, adequate resource provision, and instructor training. These findings have significant implications for the development of learning models that support learning autonomy in higher education and provide a foundation for further research into effective ways to overcome implementation challenges, particularly concerning resources and instructor training.